1982 Union Elections - Suárez Sánchez, Juan José (Hispania Nova, 2021)
The relation between the two main trades unions in Spain fluctuated during democratic transition depending on several political factors and different unions strategies, some of them based on the acceptance or the rejection of the social agreements. In the year 1982, the competition for the workers vote in unions elections was other factor that muddied the relation between UGT and CCOO, causing a bitter controversy in relation to the dates of electoral counting, with accusations of fraud, and the denial of CCOO to recognize the victory of UGT. The way off this atmosphere of confrontation was a surprising commitment of CCOO for unions unity.